2016
DOI: 10.3329/ijns.v5i2.28612
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Pattern against E. coli and Salmonella spp. in Environmental Effluents

Abstract: Hospitals (medical & veterinary) and slaughterhouse effluents were the most contaminating effluents and need to be paid more attention due to pathogenic bacteria related to animal and public health concern. Two bacterial isolates such as E. coli and Salmonella from six medical hospitals, five veterinary hospitals and five slaughter houses were isolated to find out the antibiotic resistance pattern by using disc diffusion method. The antibiotic resistance patterns of identified isolates showed that Ampicill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…One of the major findings of the study is to bacterial resistance against colistin (43.24%), which is striking and worrying. Colistin, the last resort drug, is being used extensively in agriculture and veterinary medicine [21], but its use in human medicine is restricted because of nephrotoxicity and neurotoxicity. The present study revealed that ceftriaxone, gentamicin, and erythromycin were sensitive to 56.76%, 56.76%, and 43.24% isolates, respectively, while Azad et al [20] reported 36% to gentamicin and 100% to erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major findings of the study is to bacterial resistance against colistin (43.24%), which is striking and worrying. Colistin, the last resort drug, is being used extensively in agriculture and veterinary medicine [21], but its use in human medicine is restricted because of nephrotoxicity and neurotoxicity. The present study revealed that ceftriaxone, gentamicin, and erythromycin were sensitive to 56.76%, 56.76%, and 43.24% isolates, respectively, while Azad et al [20] reported 36% to gentamicin and 100% to erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…However, all the isolates showed 100% sensitivity to colistin sulfate followed by ceftriaxone (78%) and ciprofloxacin (39%), according to Xue et al [17], who reported 52% susceptibility against ciprofloxacin. Although colistin sulfate was susceptible to all isolates in our study, the last resort drug is being used extensively in agriculture and veterinary medicine [18].…”
Section: Discussionmentioning
confidence: 96%
“…These antimicrobials are recommended to be antimicrobials of last resort for treating bacterial infections. Also, [36] reported that all their E. coli isolates were resistant against colistin. According to [37], for many decades, colistin was not recommended for use due to its toxicity and the availability of other safer antimicrobials such as penicillins.…”
Section: Discussionmentioning
confidence: 99%